The effect of indirect written corrective feedback on studentsâ writing accuracy - Shirotha, Fastha Bagus (Journal on English as a Foreign Language (JEFL), 2016)
Written corrective feedback has proven to be a key tool to improve students writing. Many previous researchers have proven so. Teacher gets to decide their very own written corrective feedback. There are many types of written corrective feedback that can be used in the classroom. They are direct written corrective feedback, indirect, and metalinguistic. The paper presents the effect of using indirect written corrective feedback to improve studentsâ writing accuracy. The paper is intended to find the best written corrective feedback strategy in the classroom. The study is conducted to 35 low-proficiency ESL students. The writing pretest and posttest are used to measure studentsâ writing accuracy. The researcher uses a t-test to analyze the data. The result is satisfying. 35 students have shown statistically significant progress in their writing accuracy. The posttest result has outscored the pretest score. Furthermore, it is also shown that indirect written corrective feedback also elicits studentsâ autonomous learning.